The History and the Creation of Standard Albanian Language and the Role of Elbasan Dialect in this Development - Myrta, Manola (Richtmann Publishing, 2012)
Every country represents and identifies itself, through its mother tongue, everywhere in the world. If we focus on thismatter,we will understand the importance of taking the so-called representative version of a language or its standard version, theexistence of every language and nation that uses it.In this context, we naturally will arise the question: When and how is created thestandard Albanian language? Which is the way that it has pursued to consolidate itself ? What were the general historical, political andsocial factors ? Which are in favor of or sometimes even a hindrance to the creation of this version ? What is the role of Elbasan dialectin this development? This study aims to present the history of the foundation of standard Albanian language starting from the earlyfourteenth century till nowadays. We will highlight the rates that have been based on two principal Albanian dialects in different historicalstages, we will also represent the general historical factors and social policy that defined â€œtoskâ€, (southern )version on which the Albanianstandard model is created. This paper will focus on the importance of Elbasan dialect or elbasanishtes, as a variant that was proposedto be settled as the official standart language, but it never becomes. We will draw out language and nonlanguage circumstances wheresuch decisions were based on and at the same time, rejected the reality. This study will help linguists who study the history and thecreation of the standard Albanian language.